March 26, 2017

Post a New Question

Posted by on .

Rules of Logarithms: Can someone explain how to do:
1) e^(2(ln)(x))
2) e^(-lnx)

I know the rules I just don't understand how they apply..

  • Trig - ,

    the "rule" here is that
    e^ln(k) = k

    so e^(2lnx)
    = e^ln(x^2)
    = x^2

    2) e^(-lnx)
    = e^ln(x^-1)
    = x^-1
    or 1/x

  • Trig - ,

    This is not the trigonometry I studied in high school

Answer This Question

First Name:
School Subject:

Related Questions

More Related Questions

Post a New Question